Pandemic Risks and Social Capital in the Context of COVID-19 - Yılmaz Ceylan; Yadigar Alus (İnsan & Toplum)
Having come to the fore intensely with late modernity risk factors have become a phenomenon the whole world has had to go through with the non-stop spread of the COVID-19 pandemic. Many situations societies had experienced that had generally affected other societies more in the past have radically changed this state in the post-traditional process. These approaches which had been theories before the spread of COVID-19 have become concrete. In this sense, the risk a society experiences in the new world order poses a risk for all societies, and dealing with this risk inevitably becomes the problem of all societies. In this process where risk is on the agenda, a non-linear relationship can be said to exist between risk and social capital, which corresponds to social communication networks, mutual trust, social support, social integration, social cohesion, and social belonging. Pandemic risks have brought people face to face with more intense problems than ever before such as illness, loneliness, and death. Many people have had trouble coping with these anomalies. This study deals with the pandemic risks that have come to the fore with COVID-19 and the phenomenon of social capital. The aims of the study are to draw attention to the effects social capital levels have on coping with risk and to mention their positive and negative aspects. The study has reached the result that the international risk resulting from the COVID-19 pandemic has caused significant negative effects and results in a short time due to its incalculability and uncertainty. In terms of coping with this situation, the need is seen to cooperate not only intra-nationally but also internationally. The result has also been reached that a non-linear relationship exists between pandemic risks and social capital.